BILL E. KUNKLE INTERDISCIPLINARY BEEF SYMPOSIUM: Temperament and acclimation to human handling influence growth, health, and reproductive responses in Bos taurus and Bos indicus cattle - Cooke, R. F. [UNESP] (Amer Soc Animal Science, 2014)
Temperament in cattle is defined as the fear-related behavioral responses when exposed to human handling. Our group evaluates cattle temperament using 1) chute score on a 1 to 5 scale that increases according to excitable behavior during restraint in a squeeze chute, 2) exit velocity (speed of an animal exiting the squeeze chute), 3) exit score (dividing cattle according to exit velocity into quintiles using a 1 to 5 scale where 1 = cattle in the slowest quintile and 5 = cattle in the fastest quintile), and 4) temperament score (average of chute and exit scores). Subsequently, cattle are assigned a temperament type of adequate temperament (ADQ; temperament score <= 3) or excitable temperament (EXC; temperament score > 3). To assess the impacts of temperament on various beef production systems, our group associated these evaluation criteria with productive, reproductive, and health characteristics of Bos taurus and Bos indicus-influenced cattle. As expected, EXC cattle had greater plasma cortisol vs. ADQ cattle during handling, independent of breed type (B. indicus x B. taurus, P < 0.01; B. taurus, P < 0.01; B. indicus, P = 0.04) or age (cows, P < 0.01; heifers or steers, P < 0.01). In regards to reproduction, EXC females had reduced annual pregnancy rates vs. ADQ cohorts across breed types (B. taurus, P = 0.03; B. indicus, P = 0.05). Moreover, B. taurus EXC cows also had decreased calving rate (P = 0.04), weaning rate (P = 0.09), and kilograms of calf weaned/cow exposed to breeding (P = 0.08) vs. ADQ cohorts. In regards to feedlot cattle, B. indicus EXC steers had reduced ADG (P = 0.02) and G:F (P = 0.03) during a 109-d finishing period compared with ADQ cohorts. Bos taurus EXC cattle had reduced weaning BW (P = 0.04), greater acute-phase protein response on feedlot entry (P <= 0.05), impaired feedlot receiving ADG (P = 0.05), and reduced carcass weight (P = 0.07) vs. ADQ cohorts. Acclimating B. indicus x B. taurus or B. taurus heifers to human handling improved temperament (P <= 0.02), reduced plasma cortisol (P < 0.01), and hastened puberty attainment (P <= 0.02). However, no benefits were observed when mature cows or feeder cattle were acclimated to human handling. In conclusion, temperament impacts productive, reproductive, and health characteristics of beef cattle independent of breed type. Hence, strategies to improve herd temperament are imperative for optimal production efficiency of beef operations based on B. taurus and B. indicus-influenced cattle.
Keywords: beef cattle; performance; reproduction; temperament